Meningkatkan Hasil Belajar Matematika Dengan Menggunakan Media Papan Musi Pada Siswa Kelas V SDK Waiara - Marianus Marton; Marianus Yufrinalis; Lukas Bera (Journal on Education, 2023)
This research is a class action research (PTK) carried out in two cycles. The purpose of this study is to determine the application of Papan M usi media in improving the ability of students to calculate KPK on fractional addition and subtraction materials in class V SDK Waiara students and to find out the results after applying musi board media to the material of addition and subtraction of fractions in class V students of SDK Waiara. The data needed in this study are quantative and qualitative data consisting of learning outcomes data, observation results on learning implementation, rubric of assessment of results and process assessment. These data are sourced from students and researchers. This data analysis is carried out using quantitative and qualitative analysis. Quantitative analysis is used to explain the success rate of students in searching for KPK on fractional addition and subtraction materials. Quality analysis is used to explain changes in the behavior of students and researchers in the learning process. The results showed that the use of Musi Board media in looking for KPK in the material of addition and subtraction of fractions can improve the learning outcomes of class V students in the first semester of SDK Waiara for the 2022/2023 academic year. This is shown by the percentage of student completion of 69.230% in cycle I increased to 92.31% in cycle II.